2009
DOI: 10.1053/j.gastro.2009.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities in ICC Ca2+ Activity Within Canine Large Intestine

Abstract: Background & Aims In human and canine colon, both slow (slow waves, 2–8/min) and fast (myenteric potential oscillations; MPOs, 16–20/min) electrical rhythms in the smooth muscle originate at the submucosal and myenteric borders, respectively. We used Ca2+ imaging to investigate whether ICC at these borders generated distinct rhythms. Methods Segments of canine colon were pinned submucosal or myenteric surface uppermost, or cut in cross-section. Tissues were loaded with a Ca2+ indicator (fluo-4) and activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…The amplitude of the average Ca 2ϩ transient of the second wave was reduced compared with the initial wave. The relationship between frequency and amplitude of Ca 2ϩ waves is similar to what has been described in the colon (32) and is likely the result of the time needed to refill intracellular Ca 2ϩ stores. The velocity of propagating Ca 2ϩ waves averaged of 2.7 Ϯ 0.27 mm/s (n ϭ 19).…”
Section: Resultssupporting
confidence: 72%
“…The amplitude of the average Ca 2ϩ transient of the second wave was reduced compared with the initial wave. The relationship between frequency and amplitude of Ca 2ϩ waves is similar to what has been described in the colon (32) and is likely the result of the time needed to refill intracellular Ca 2ϩ stores. The velocity of propagating Ca 2ϩ waves averaged of 2.7 Ϯ 0.27 mm/s (n ϭ 19).…”
Section: Resultssupporting
confidence: 72%
“…The decrease of ICC, as observed in several motility disorders (13,17,21,24,25,34), reduces amplitudes of slow wave and, consequently, induces intestinal dysmotility by reducing electrical drive to smooth muscle contractions and peristalsis (38). A recent study has shown that the number and volume of ICC networks in the normal human stomach and colon declined with age using IHC analysis, but related molecular analysis, such as Western immunoblotting or real-time PCR, was absent in that study (15).…”
Section: Discussionmentioning
confidence: 85%
“…The study of the electrophysiology of human colonic muscle is obviously in its infancy. In contrast with subserous ICC in mouse, guinea pig, canine, and nonhuman primate colon [Toma et al, 1999;Vanderwinden et al, 2000b;Aranishi et al, 2009;Lee et al, 2009;Chan et al, 2010;Han et al, 2010;Blair et al, 2012a], but in accordance with subserous interstitial cells in mouse internal anal sphincter [Cobine et al, 2011], IC-SS of the human colon are apparently Kit negative [He et al, 2000;Pieri et al, 2008;Liu et al, 2012]. ICC in murine, nonhuman primate, and human GI tracts express ANO 1, a Ca ++ -activated Cl -channel which is encoded by the transmembrane protein Tmem 16a [Gomez-Pinilla et al, 2009;Hwang et al, 2009;Kashyap et al, 2011;Sanders et al, 2011;Blair et al, 2012b].…”
Section: Discussionmentioning
confidence: 99%
“…In mouse colon we previously described c-kit-positive subserous ICC with an ultrastructure similar to colonic ICC at the myenteric plexus [Vanderwinden et al, 2000b], and a similar cell type may be present in guinea pig colon [Toma et al, 1999;Aranishi et al, 2009] as well as in canine colon [Lee et al, 2009]. The latter study on canine colon may have provided the first clue to a function of these cells, since it appeared that Ca ++ waves where initiated in subserous ICC and propagated towards ICC at the myenteric level through longitudinal muscle.…”
mentioning
confidence: 99%